Mechanism of comparison in the structure of self-efficacy in junior athletes` - Raievska, Y.; Savchuk, O.; Hulias, I.; Khokhlov, A.; Hoian, I.; Syniakova, V.; Soroka, O.; Lukashov, O. (Journal of Physical Education and Sport, 2024)
This theoretical and empirical research examines the mechanism of comparison within the framework of self-efficacy in junior athletes` sporting activities. The study included junior athletes of varying levels of qualification, participants in international, European, World, and Olympic sports competitions, aged 15 to 19 years. The sample parameters were as follows: n = 114; M = 17.91 years; SD = ±3.43; Me = 18.00.